2013
DOI: 10.1097/spv.0b013e318278cc40
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Cytologic Effects of Vaginal Estrogen in Women With Pelvic Organ Prolapse

Abstract: Preoperative vaginal estrogen application for 2 to 12 weeks restores vaginal cytology to premenopausal levels, but does not increase vaginal epithelial thickness in women with prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Among women planning to undergo surgical repair for prolapse, three studies have reported on preoperative vaginal oestrogen by various methods, compared with placebo or no treatment, with a total of 111 participants. [10][11][12] Follow-up varied from 12 weeks to 3 years of postoperative surveillance. No vaginal oestrogen was given following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among women planning to undergo surgical repair for prolapse, three studies have reported on preoperative vaginal oestrogen by various methods, compared with placebo or no treatment, with a total of 111 participants. [10][11][12] Follow-up varied from 12 weeks to 3 years of postoperative surveillance. No vaginal oestrogen was given following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10 They suggested that if vaginal oestrogen does improve tissue integrity then therapy may need to be continued postoperatively until the time of complete scar maturation. 12 There is no clear evidence to state how long when a women would have adequate scar maturation after a prolapse surgery as this could be dependent on various factors of wound healing. In the current study, women in the intervention group continued oestrogen up to 20 weeks postsurgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in an RCT by Karp et al, using an estradiol-releasing ring 2 weeks (for 12 weeks) after pelvic floor repair resulted in improved markers of tissue quality including slightly reduced urinary tract infections compared with placebo [ 27 ]. In a study evaluating the role of 2–12 weeks’ preoperative local estrogen in increasing vaginal wall thickness prior to POP surgery, there was no statistically significant increase in the thickness of the vagina in the treatment group compared with the group with no intervention [ 28 ]. Similar, Rahn et al summarized in an SR that it is uncertain whether preoperative vaginal estrogen is beneficial before prolapse repair as no increased vaginal subepithelial or muscularis thickness could be observed (low quality) [ 16 ].…”
Section: Role Of Local Estrogens In the Treatment Of Pelvic Floor Dismentioning
confidence: 99%